(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Vegetables are present an important part of the human daily diet in almost any culture of the world. Market is a place where people can buy easily with reasonable price. Weekly market arranged in specific area on specific day to sell the goods. Vegetables vendors are more in weekly market. They purchase vegetables from main market. Financial poor vendors are selling the goods in weekly market. They get daily income which can be used for domestic as wellas commercial according to their needs. This paper shows the buyers behavior towards weekly market. It is found that head of the family is controlling the house and providing the requirement of food items from the nearly weekly market. It is a place of getting fresh vegetables. It provides employment opportunity to the micro entrepreneurs with low investment. Evening time is better for the vendors as well as customers. Weekly market saves the time and money which helps the both vendors and customers. Male and females customers also come to the market. They purchase vegetables according to weekly requirements. They need not to visit market every day. It also save the time and transportation expenses. This research paper is to be discussed about “Consumer Perception of Local weekly Markets – A Study on Weekly Market in Hyderabad.”